(untitled) (Research, Society and Development, 2020)
Brazil has a great biodiversity of varied species in flora and fauna in its diverse ecosystems. Indigenous peoples and traditional populations, in some way, are primarily responsible for the conservation and biological diversity of our ecosystems, a product of the interaction of nature management in traditional models. This work aimed to register the traditional uses of “Terramicina” Alternanthera dentata (Moench) Stuchlik., In the community of Bacuriteua, besides of course registering the botanical information, as well as describing the active principles present in the plant, in order to contribute to the maintenance popular knowledge and the conservation of this species. The methodology was based on a qualitative approach, through field research employing data collection techniques with free listing, interviews with key informants, forms, observation and collection of plant samples for later identification. From the results of the research, it was registered that the researched community has a wide knowledge in relation to the use of medicinal plants, more precisely the “Terramicina”, since the species is used for the treatment of headache, injuries, allergies and urinary tract infection. Thus, it is important to disseminate such knowledge to future generations, in addition to the importance of the coherent use of medicinal species.